2015
DOI: 10.14260/jemds/2015/1085
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Maternal Care Practices in Tribal Area and Urban Slums

Abstract: INTRODUCTION:Mothers and children constitute the major proportion of our population. At the same time these two groups are very vulnerable and require special attention in health care. 1 In spite of progress in health care delivery, there are variations in utilization of the health services in urban slums, rural and tribal areas. Therefore in this context, an attempt was made to compare the health care practices of mothers in tribal area and urban slums. MATERIAL AND METHODS: The study is a community based cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Prior research is suggestive of preference of government health facility over private sector, especially for antenatal care and chronic diseases. [ 8 9 10 11 12 ] There is also enough evidence to show the inclination toward private practitioners for acute/minor illnesses. [ 13 14 15 16 ] This may be attributed to the fact that majority of the patients have started seeking immediate treatment on falling ill and these are more accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research is suggestive of preference of government health facility over private sector, especially for antenatal care and chronic diseases. [ 8 9 10 11 12 ] There is also enough evidence to show the inclination toward private practitioners for acute/minor illnesses. [ 13 14 15 16 ] This may be attributed to the fact that majority of the patients have started seeking immediate treatment on falling ill and these are more accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Issues such as ignorance, illiteracy, strong adherence to beliefs, geographic locations, lack of accessibility and non availability or utilization of health services contribute to poor neonatal health outcomes. [3][4][5] Each tribe has its own newborn care rearing practices. Available studies on newborn care practices of tribes have reported beneficial and harmful customs.…”
Section: Introductionmentioning
confidence: 99%
“…Very little information is available in this issue among the tribes in Tamilnadu, which habitats about 1% of the 10.42 crores tribal population of India. [3][4][5][6][7] In this context, an attempt was made to understand the neonatal care practices prevailing in a selected tribal region of Tamilnadu, India.…”
Section: Introductionmentioning
confidence: 99%